Analisis Faktor – Faktor Yang Mempengaruhi Turnover Intention Pada Karyawan Hotel - Habibie, Fachrul Husain; Sabrina, Bella (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2018)
This research was conducted with the aim to determine what factors influence Turnover Intention. And to find out the employee's assessment of psychological contract, job satisfaction, organizational commitment, job insecurity, wages, company size, age and tenure of Turnover Intention. The research method used in this study is the method of validity, reliability, mean, cartesian diagram, GAP, and CSI, and with the survey method that uses questionnaires as a data retrieval tool. As well as the unit of analysis used is individuals in this case are employees of Hotel XYZ totaling 136 respondents. The results of the data obtained will be processed through the SPSS program tool ver 23. After the data collection has been carried out and the data is processed, the results obtained are the quality of the company that has been considered good enough by the employees. But there are some things that must be corrected. The results are still lacking by employees, namely the expectation of employees who are considered lacking with a value of -0.91, that is, professionals in work are still considered lacking, - 0.85, namely that work safety is still considered insufficient, and - 0.82 ie salary which is appropriate for the employee's work. With the results data above, these three factors are still considered lacking by employees, while for other factors it is considered good enough by employees.